Marx and Modern Law - Poulantzas, Nicos (1970)
In order to explain the general principles of a Marxist analysis of law, it is important to analyze, from a critical perspective, the deformations that the Marxist theory of law has undergone over a long period of time. In this way, these deformations affect both the theory and the politics of Marxist thought, and are mainly manifested in two currents: the economic and the voluntarist. The author points out that the first deformation redirects the juridical level to an economic conception, while the second reduces law to the will of the dominant political class. In this context, in order to recover the original content of Marxist thought, which provides us with the tools for a study of law as a complex structure that affects social relations, it is necessary to take a look at the modern law that emerges with capitalism. Thus, the author concludes by pointing out that Marxism cannot be separated from its scientific and political aspect, and that modern law is related to the exploitation and domination of the bourgeois class; however, the author rejects that the link between law and class domination can be reduced to the will of the ruling class.